DILEMA KONSUMSI DI TENGAH BOIKOT: MENGAPA KONSUMEN MASIH MEMBELI PRODUK STARBUCKS? Analisis Faktor Keputusan Pembelian atas Produk yang Diboikot di Kota Makassar - Achmad Ridha; Wiwin Riski Windarsari; Azlan Azhari; Lidya Anastasya (Politeknik Negeri Ambon, 2025)
Introduction: This study investigates the factors influencing consumer decisions to continue purchasing Starbucks products in Makassar amid active boycott campaigns linked to geopolitical issues. The phenomenon reflects the rise of political consumerism, where moral, ideological, and social values intersect with consumption behavior. Despite mounting public pressure, many consumers persist in their consumption habits, raising questions about the psychological and social drivers that shape these decisions. Methods: This quantitative study employed Exploratory Factor Analysis (EFA) to examine data collected through Likert-scale questionnaires distributed to 180 respondents. The 18 indicators used in the instrument were derived from relevant literature, previous research, and preliminary observations. The aim was to identify the underlying dimensions that explain why consumers remain loyal to a brand under socio-political pressure. Results: The factor analysis identified four key dimensions: (1) Emotional Attachment and Brand Perception, (2) Social Influence and Environmental Pressure, (3) Psychological Response to Boycott, and (4) Autonomy and Self-Identity. The findings reveal that emotional loyalty, product satisfaction, and perceived quality strongly influence continued purchasing behavior. Additionally, mechanisms such as cognitive dissonance and symbolic resistance help consumers rationalize their decisions, while weak social pressure and personal autonomy further support brand loyalty. These results suggest that consumer resistance to boycott appeals is shaped by complex interplays between psychological attachment, social context, and self-image. Keywords: Consumer Decision, Political Consumerism, Boycott, Brand Loyalty, Exploratory Factor Analysis